Conventional IVF as a laboratory strategy to rescue fertility potential in severe poor responder patients: the impact of reproductive aging. (November 2013) - Artini, Paolo Giovanni; Obino, Maria Elena Rosa; Carletti, Elena; Pinelli, Sara; Ruggiero, Maria; Di Emidio, Giovanna; Cela, Vito; Tatone, Carla
Abstract Objective: To investigate whether laboratory strategies can improve in vitro fertilization (IVF) outcome in poor responder patients. We compared the effectiveness of conventional IVF and intra cytoplasmic sperm injection (ICSI) in assisted reproductive technologies cycles in which only one or two oocytes were retrieved at ovarian pick up, in the absence of male infertility. Design: Retrospective analysis of 425 cycles in 386 poor responder patients. Intervention(s): Standard stimulation protocol with gonadotropins and gonadotropin releasing hormone (GnRH) antagonist. Main outcome measure(s): Fertilization rate, cleavage rate, good-quality embryo rate, implantation rate, clinical pregnancy rate (PR) and miscarriage rate. Results: IVF was found to be more advantageous for implantation and PR, especially in patients under 35 years and in women aged between 35 and 38 years. No differences were noted in the other parameter evaluated. Patients aged over 38 years showed no difference using the two techniques. Conclusion: The employment of ICSI in the absence of a male factor can reduce reproductive outcome in poor responder. Probably because of aging-related defects overcoming the advantage of sperm selection, the choice of IVF technique is not relevant to reproductive success when oocyte quality is compromised by reproductive aging. Although further randomized trials are needed to confirm our results, we propose that, in absence of male infertility, conventional IVF might be the technique of choice in young patients, especially in those aged below 35 years.